CLEANLINESS: INDIA'S CHALLENGE: स्वच्छताः भारत की चुनौती - Pandey, Pragya; Yadav, Garima (International Journal of Research -GRANTHAALAYAH, 2015)
Cleanliness and health are the basis of the progress of any country. Clean environment helps in elevating the health status of any community. Clean environment can be helpful in improving the standard of living of the people of the community. He is also capable of breaking the cycle of diseases in the community. Various resources are being used by the efforts and participation of the government and general public and are trying for better results. Through this, the socio-economic development of the community, cultural factors related to clean environment, the capacity of the community, behavior, laws, etc. are being used in a better way. India is far behind in the level of clean environment all over the country. Uncleanness still holds India in its grip, to break out of which India needs to work unitedly on issues of hygiene and health and implement various strategies and programs, so that the goals are successfully achieved at the grassroots level. Can be obtained. Different types of strategies are being devised at the central and state level to get out of the vicious cycle of impurity. A clean environment is the only way for the community to break the cycle of various diseases. किसी भी देश की उन्नति का आधार स्वच्छता व स्वास्थ्य है। स्वच्छ पर्यावरण ही किसी भी समुदाय की स्वास्थ्य स्थिति को ऊंचा उठाने में सहायक है। स्वच्छ पर्यावरण समुदाय के लोगों के जीवन स्तर को सुधारने में सहायक हो सकता है। साथ ही वह समुदाय मंे रोगों के चक्र को तोड़ने में भी सक्षम है। सरकार व आम जनता के प्रयास व सहभागिता द्वारा विभिन्न संसाधनों का प्रयोग किया जा रहा है और बेहतर परिणाम हेतु प्रयासरत हंै। इसके द्वारा समुदाय का सामाजिक-आर्थिक विकास, स्वच्छ पर्यावरण हेतु संबंधित सांस्कृतिक कारक, समुदाय की क्षमता, व्यवहार, कानून आदि का उपयोग बेहतर तरीके से हो रहा है। भारत देश सम्पूर्ण में स्वच्छ पर्यावरण के स्तर में बहुत ही पीछे है। अस्वच्छता ने आज भी भारत को अपने घेरे में जकड़ लिया है, जिसमें से बाहर निकलने के लिए भारत को स्वच्छता व स्वास्थ्य के मुद्दें पर एकजुट होकर काम करने व विभिन्न रणनीतियों व कार्यक्रमों को क्रियान्वित करने की आवश्यकता है, जिससे लक्ष्यों को जमीनी स्तर पर सफलतापूर्वक प्राप्त किया जा सके। अस्वच्छता के कुचक्र से बाहर निकलने के लिए केन्द्र व राज्य स्तर पर विभिन्न प्रकार की रणनीतियां बनायी जा रही है। स्वच्छ पर्यावरण ही समुदाय को विभिन्न रोगों के चक्र को तोड़ने में सक्षम है।